Computational modeling of the aerodynamic characteristics and flight mechanics and control of an unmanned aerial vehicle - Tan, Leon Mark Choon Seng (2010)
This thesis outlines the effort in developing an integrated simulation framework for assessing the stability and control characteristics of an Unmanned Aerial Vehicle (UAV). The objectives are to understand flight instabilities experienced by the UAV and to propose solutions for the flight stability and control problems via an integrated modeling framework. The basic core of the framework involves the incorporation and integration of the UAV aerodynamic characteristics, flight stability derivatives and digital flight control system, into a six degree-of-freedom flight simulation model, the outputs of which are visualized graphically. To support the development of the simulation model, a comprehensive aerodynamic database for the UAV is required. Empirical aerodynamic estimation software such as USAF Digital Datcom and computational flow simulation software suites such as FLUENT and Solidworks Flo Works have been used to estimate the aerodynamic force and moments as well as stability and control derivatives of the UAV. By combining these estimates with wind tunnel data, a comprehensive aerodynamic characteristics model is constructed for augmenting the flight dynamics model of the UAV. Initially, a de-coupled longitudinal and lateral stability analysis based on the small disturbance theory has been developed to understand the stability modes of the UAV. A coupled longitudinal and lateral stability analysis was then developed to study the effects of the aerodynamic coupling caused by the single propulsion system to the stability and control characteristics. The model is created within the programmable software environments of Matlab®, Simulink® and Aerospace Blockset® which are used to construct the six-degree-of-freedom model for the dynamical motion of the UAV. The inputs to the model include the aerodynamic information based on the aerodynamic characteristics, stability derivatives, engine characteristics, flight variables and atmospheric disturbances.